A proposed high voltage distribution system for Mu2e electron tracker. (1st March 2022) - Ahmed, W.; Hungerford, Ed.; MukeherJee, A.; Russu, V.; Tschirhart, R.; Yucel, M.; ,
Abstract: This paper reports on the design and construction of a High Voltage Distribution System (HVDS) for a "Smart Switch" developed to provide high voltage (HV) to a series of stacked straw detector planes in the Mu2e Electron Tracking Detector (ETD). Each plane is composed of three 120 deg. Crescent-shaped panels, and each panel is composed of 96 straw tubes. The HVDS provides HV on-off, current monitoring, recording, and crowbar for over-current protection. The inter-communication system is based on TCP/IP. The HVDS supplies HV with long term stability, and accurately monitors the applied voltage and currents.